Changes in clinical scenarios, management, and perspectives of patients with chronic hepatitis C after viral clearance by direct-acting antivirals. (3rd June 2021) - Nevola, Riccardo; Rinaldi, Luca; Zeni, Letizia; Romano, Ciro; Marrone, Aldo; Galiero, Raffaele; Pafundi, Pia Clara; Acierno, Carlo; Vetrano, Erica; Adinolfi, Luigi Elio
ABSTRACT: Introduction: Hepatitis C virus (HCV) causes a systemic infection inducing hepatic and extrahepatic diseases. These latter involve cardiovascular system, kidney, brain, endocrine, glucose, and lipid metabolism, and the immune system. HCV infection is associated with an increased risk of morbidity and mortality for both hepatic and extrahepatic events. Direct-acting antivirals (DAA), introduced in the most recent years for HCV treatment, are effective in up to 99% of cases and have changed the clinical scenarios and management of these patients. Areas covered: The literature on the impact of HCV clearance by DAA on both hepatic and extrahepatic disease outcomes has been analyzed and discussed in this review in order to summarize the full therapeutic potential and its weaknesses. Expert opinion: Patients achieving HCV clearance have improved hepatic and extrahepatic diseases, quality of life and survival. They have lower incidence of cardiovascular disease, type 2 diabetes, kidney damage, and immuno-mediated manifestations. However, the improvements are related to the degree of pre-treatment organ damage. Therefore, a significant percentage of patients with advanced disease remains at risk of morbidity and mortality and must be monitored in the post-treatment. In addition, data emphasize the importance of starting treatment during the early stages of HCV infection.